Interpersonal communication-, education- and counselling-based interventions to support adherence to oral anticancer therapy: a systematic review. (March 2023) - Elston Lafata, Jennifer; Nguyen, Bobbie; Staresinic, Claire; Johnson, Morgan; Gratie, Daniel; Muluneh, Benyam
Background. Many factors contribute to oral anti-cancer therapy adherence, including counselling and educational support.Objective. We systematically review the literature evaluating the effectiveness of interpersonal communication-, counselling- and education-based interventions on patient adherence to oral anticancer therapy.Methods. Using search terms pertaining to medication adherence, oral anticancer therapy, and communication, education, and counselling, we conducted a systematic search for full-text, original research articles prior to 3/13/20. Two reviewers independently reviewed each paper for inclusion and charted study information.Results. Twenty-four articles were included. All considered the use of oral anticancer therapy between two defined time points. Four studies also considered the length of time a patient persisted on therapy. Half ( n = 12) of the studies reported a statistically significant relationship between the intervention and medication adherence, with no consistent pattern among intervention structure/content and effectiveness. Programmes offering in-person counselling and those targeting patients with chronic myeloid leukemia (CML), tended to report positive findings. Most studies faced substantial risk of bias, and only two reported using a behavioural theory to guide interventional content.Conclusions. Findings highlight the infancy of evidence base and need for rigorous and large-scale studies grounded in established behavioural theories to advance patient-targeted educational and counselling practices supporting adherence to oral anti-cancer therapy.